Real-time monitoring system based on integration of internet of things and global system of mobile using Raspberry Pi - Hamzah H. Qasim; Ali M. Jasim; Khalid A. Hashim (Bulletin of Electrical Engineering and Informatics, 2023)
Security and safety of homes remain critical issues in all countries. The majority of individuals have to deal with significant issues like fire and theft at some point in their lives, particularly in families that spend the majority of their time and engage in most of their activities outside the house. There is a pressing need to use cutting-edge technology in order to upgrade and strengthen the security system, as well as to remotely monitor the living environment for potential mishaps. In this paper, we proposed two integrated techniques, which are the internet of things (IoT) and short message service (SMS), to monitor the home for hazards to take the necessary actions, by Raspberry Pi 4 model B as a controller and phone app to monitor. Global system of mobile (GSM) sends SMS alerts to users, and the Blynk application monitors the data of sensors. Our outcome of this demonstrates that the proposed had the capability and high efficiency to monitor and detect undesirable situations in real-time before disasters occur.